TINGKAT ADOPSI DAN DIFUSI INOVASI BETERNAK AYAM BROILER DI KOTA KENDARI - Abdullah, Sukmawati (Jurnal AGRISEP, 2011)
This study is aimed to know the adoption level and breeders’ diffusion to the innovation of breeding Broiler chicken in Kendari city. The analysed method used is descriptive analysis method.  Seventy breeders are cencused to get data related to their innovation adoption. The result of the research shows that most of the breeders have productive age, moderate family responsibility, and categorized as small scale breeder due to their limeted number of owned livestock. The reseach also find that characteristic of brochure media, most of the respondents are easy to understand the contents of the brochure which are suitable with their need.  They also said that brochure is presenting in an interesting wa.  Furthermore, only a few breeders have high adoption level.  It means that the breeders have not applied comprehensively the innovation components of breeding Broiler chicken, such as: using day old chick, caging, and growing.